Novel macroporous amphoteric gels: Preparation and characterization - S. Kudaibergenov; Zh. Adilov; D. Berillo; G. Tatykhanova; Kh. Abdullin; Zh. Sadakbaeva; I. Galaev (eXPRESS Polymer Letters)
Macroporous amphoteric gels based on allylamine, methacrylic acid and acrylamide crosslinked by N,N'-methylenebisacrylamide were synthesized by radical copolymerization of monomers in cryoconditions. The composition of cryogels was determined by combination of potentiometric and conductimetric titrations. The morphology of cryogels was evaluated by scanning electron microscope (SEM). Cryogels exhibited sponge-like porous structure with pore size ranging from 50 to 200 μm. The values of the isoelectric points (IEPs) determined from the swelling experiments arranged between 3.5 and 4.3. The high adsorption-desorption capacity of amphoteric cryogels with respect to mM and trace concentrations of copper, nickel, and cobalt ions was demonstrated. It was shown that the macroporous amphoteric cryogels are able to adsorb up to 99.9% of copper, nickel, and cobalt ions from 10–3 mol•L–1 aqueous solution.